Regional Determinants of Child Mortality in Nigeria: Evidence from Survival Analysis - Haganawiga, Kumur John; Pal, Surya Kant; Sirohi, Anu (International Journal of Child Health and Nutrition, 2025)
Objective: This study investigated regional determinants of child mortality in northern Nigeria, focusing on socio-economic, demographic, and environmental factors. Methods: Data from the 2018 Nigerian Demographic and Health Survey (NDHS) on 10,400 under-five children were analyzed. Kaplan-Meier survival curves and the Cox Proportional Hazards model assessed survival probabilities and risk factors. However, the proportional hazards (PH) assumption was violated (χ² = 1190.00, df = 13, p < 2e-16), indicating time-varying effects. Consequently, the Weibull model was used for a more precise estimation. Results: Kaplan-Meier estimates revealed significant regional disparities in child survival (p < 0.0001), with North Central having the highest survival, North East intermediate, and North West the lowest. The log-rank test (χ² = 176.214, p < 0.001) confirmed these differences. The Weibull model identified male children as having a higher mortality riskcompared to female children, likely due to biological vulnerabilities and variations in healthcare. Larger households and shorter birth intervals increased mortality risk due to resource constraints. In contrast, improved sanitation and clean water access significantly reduced mortality. Higher maternal education, household wealth, and breastfeeding were strongly associated with better survival. Notably, not breastfed children had a 45%, 46%, and 49% higher mortality risk across regions. Birth intervals exceeding 35 months and maternal age at first birth between 29 and 36 years improved survival. Conclusion: These findings emphasized the need for policy interventions, including family planning, improved sanitation, maternal education, and breastfeeding promotion, to reduce child mortality and regional disparities in Nigeria.